An Experimental Study on the Theorem of Non-Vertical Axes in Determining the Moment of Inertia of Hard Objects Using a Physical Pendulum - Khawari, Rajab Ali (Journal of Natural Sciences – Kabul University, 2023)
The theorem of vertical axes is widely used in calculating the moment of inertia for one-dimensional and two-dimensional objects. It is equally applicable to three perpendicular axes. This study explores its applicability in non-vertical positions by conducting experiments on narrow non-vertical bars. The findings confirm that the theorem holds true in non-vertical scenarios as well. Physical pendulums were employed for experimental investigations of vibration periods, and theoretical calculations were developed. These resulted in data and graphs with an approximate error of less than 1% across all experimental stages. The results were assessed through numerical and graphical analyses, with differences consistently below the relative error margin.